High prevalence of prolonged QTc interval among individuals in ambulatory diabetic care in southwestern Uganda - Migisha, Richard; Agaba, David Collins; Katamba, Godfrey; Miranda, Silvia Lopez; Muyingo, Anthony; Siedner, Mark J. (International journal of diabetes in developing countries, 2021)
Heart rate-corrected QT (QTc) interval is associated with increased risk for cardiovascular events and mortality among individuals with diabetes mellitus (DM). Little is known about the epidemiology of prolonged QTc among people with DM in resource-limited settings. Methods We conducted a cross-sectional study among adults with diabetes in ambulatory care at the Mbarara Regional Referral Hospital, from November 2018 to April 2019. Twelve-lead ECG recordings were performed on all participants. We collected clinical and laboratory data related to diabetes disease status and treatment control.We estimated QTc using Bazett’s formula and categorized it according to standardized sex-adjusted thresholds. Linear regression analysis was performed to identify correlates of QTc. Results We recruited 299 participants with a mean age of 50.1 years (SD±9.8) and mean HbA1c of 9.7 % (SD±2.6), and 69.6% were female. We detected prolonged and borderline QTc in 6.4% (19/299, 95% CI: 3.9–9.7%) and 23.4% (70/299, 95% CI: 18.7–28.6%) of participants, respectively. In multivariate models, factors associated with increasing QTc interval were mean arterial pressure (β=0.34; 95% CI: 0.07–0.63, p=0.019) and female sex (β=15.26; 95% CI: 7.58–22.94, p<0.001). Conclusions The prevalence of abnormal QTc among individuals in routine diabetes care in southwestern Uganda was high. Female sex and mean arterial pressure were correlated with QTc interval. Given these findings, future studies should explore the clinical impact of abnormal QTc in this patient population.
Keywords: QT interval; Prevalence; Diabetes; QTc dispersion; QTc prolongation